Serum IgE levels are a risk factor with prognosis of pediatric minimal change disease - Han, Tingting; Xue, Mei; Guan, Yafei; Ju, Tao; Shi, Kaili; Fu, Mengzhen; Jia, Lili; Gao, Chunlin; Xia, Zhengkun (Frontiers in Pediatrics, 2023)
Background: Minimal change disease (MCD) is one of the most common primary glomerular disorders with high serum IgE levels. This study was aimed to investigate the clinical features of different serum IgE levels in pediatric MCD and evaluate prognostic significance of serum IgE levels in regard to remission and relapse in pediatric cohort.Methods: This study enrolled 142 new-onset children diagnosed with biopsy-proven MCD from January 2010 to December 2021 at Jinling Hospital in Nanjing, China. These cases were divided into three groups according to serum IgE levels. MCD patients' demographics, clinical parameters and follow-up data were collected and analyzed. The primary and secondary outcomes were defined as the time to the first complete remission (CR)and the first relapse.The results manifested that 85.2% (121/142) MCD children had high serum IgE levels (IgE > 90.0 IU/mL). 142 patients were divided into the normal-, low-and high-IgE groups based on the normal reference value level (90.0 IU/mL) and median serum IgE level (597.5 IU/mL). The high-IgE group have a significantly lower cumulative rate of the first CR (Log-rank, P=0.032) and a higher rate of the first relapse (Log-rank, P=0.033) than normal-IgE and low-IgE group. Multivariate Cox analysis showed that IgE≥597.5 IU/mL was independently associated with the delayed first CR (hazard ratio [HR]= 0.566, 95% confidence interval[CI]= 0.330 -0.972, P= 0.039) and the early first relapse (HR =2.767, 95% CI=1.150-6.660, P=0.023).Conclusions: Serum IgE levels were an independent correlation factor for pediatric MCD delayed remissions and early relapses.